A minimally sufficient analysis of sufficiency modal constructions - Condoravdi, Cleo; Francez, Itamar (Proceedings of the Amsterdam Colloquium, 2022)
A well-known compositionality problem involves the interaction between only and goal oriented modality: only can weaken a necessity statement and a necessity modal can suspend a characteristic inference associated with only, the inference to the prejacent. Existing proposals resort to non-standard assumptions either about only or what it combines with. We show that a standard analysis of only and a plausible analysis of goal-oriented modality can account for the compositionality problem.